Mathematical Creative Thinking Ability Based on Intellectual Intelligence and Cognitive Style in SSCS Learning with Open-Ended Problems - Probosiwi, Wdyanita Indah; Suyitno, Hardi; Dwidayati, Nur Karomah (Unnes Journal of Mathematics Education Research, 2021)
The study aims to describe the mathematical creative thinking ability reviewed from intellectual intelligence and cognitive style in SSCS learning with open-ended problems. This research is a type of mix method research with sequential explanatory design. The population of this research is a class VII student of State Junior High School 3 Semarang academic year 2018/2019. Sampling method used in this study was random sampling technique. The study subject was selected with the purposive sampling technique based on the results of the intellectuality intelligence and the field independent (FI) cognitive style or the field dependent (FD). The results showed that the group of upper normal intelligence students category with the cognitive style of FI reaches the four indicators of mathematical creative thinking ability so that they are included in Level 4 (very creative), the group of upper normal intelligence students categorywith the cognitive style of FD can achieve three indicators of mathematical creative thinking ability and included in Level 3 (creative), the group of normal students category with the cognitive style of FI can achieve two indicators of mathematical creative thinking ability which then is included in Level 2 (quite creative), and the group of normal students category with the cognitive style of FD is only able to achieve a single indicator of mathematical creative thinking ability so that it is included in Level 1 (less creative).